Issues in determining factors influencing bacterial attachment: A review using the attachment of Escherichia coli to abiotic surfaces as an example - Goulter, R.; Gentle, I.; Dykes, Gary (Blackwell Scientific Publishers, 2009)
Summary An understanding of the mechanisms which facilitate the attachment of Escherichia coli and other bacterial species to abiotic surfaces is desired by numerous industries including the food and medical industries. Numerous studies have attempted to explain bacterial attachment as a function of bacterial properties such as cellular surface charge, hydrophobicity and outer membrane proteins amongst others. Conflicting evidence in the literature both for and against a positive relationship may arise from the nature of the test methods used to measure them. A handful of recent studies utilizing technologies such as atomic force microscopy have begun to look at bacterial attachment at a single cell and molecular level. These studies may provide the information required to fully understand the underlying factors which influence bacterial cell attachment to abiotic surfaces. A number of issues in determining the influential factors of bacterial attachment have been identified from the literature: a lack of standardization and sensitivity of methods, as well as the value of measuring bulk properties of a number of cells rather than the behaviour of single cells which may overlook key interactions at a molecular level. These issues will need to be addressed in future studies in this area. © 2009 The Society for Applied Microbiology.